Synthesis of the switching control law for a quadrotor autopilot - Kucherov, Dmytro; Sushchenko, Olha; Rasstrygin, Alexander; Zhdanov, Serhii; Kozub, Andrei (International Journal of Engineering and Technology, 2018)
The paper deals with the problem of synthesizing the time-optimal control law by the angular coordinates of an unmanned aerial vehicle with stabilization in the pitch and roll directions. The full mathematical model of the unmanned aerial vehicle is reduced to a system of the first-order differential equations, based on which the optimal control law is constructed. Control action in each plane depends only on the measured coordinates and is calculated in real time. It is believed that the dynamic model, described by a system of differential equations, contains complex roots, which indicate the oscillatory response of the controlled object to the control action. Some properties of the switching line and switching control are also considered in the paper. Some results of simulating the dynamics of the object under examination with a synthesized control law are presented.